Corporate Social Responsibility as a Tool for Employer Branding and Accounting Disclosures - Miljan Adamović; Stefan Milojević; Aleksandra Mitrović (BizInfo)
Corporate social responsibility is seen as an integral part of business, and organizations should sincerely include social duties towards internal and external stakeholders in their operations. It is essential for employers to focus on deepening the bond between the employer and staffs, as employees are a crucial group of stakeholders. The aim of the research of this paper is to point out the strategic and operational links between employer branding and socially responsible business in family businesses and to bring attention to the importance of accounting disclosures in that context. In order to determine how corporate social responsibility is used in employer branding in a practical environment, an analysis of activities related to socially responsible business as a tool of employer branding in family businesses was conducted.